SCRUTINIZING THE IMPACT OF POPULAR CULTURE ON GENERATION Z’S ENGLISH - Aprilia Ridadi Prihatini; Aam Alamsyah; Agus Udong Rapiudin (Jurnal Media Akademik (JMA), 2025)
The present study aimed to investigate the influence of popular culture on Generation Z and their English proficiency. The research method was qualitative, and the participants were ten young people categorized as Generation Z. The participants were recruited purposely. There were two research questions: a) How does Generation Z view popular culture? b) How do widespread popular cultures impact Generation Z’s English? The data analyzed were the participants’ verbal responses, recorded by the researcher. The findings suggest that the influence of popular culture on social media among Generation Z was substantial. For instance, the generation was found to actively participate in listening to songs, watching movies, or creating their own cultures. Generation Z’s English was also found to have improved due to exposure to popular culture on social media. Additionally, participants noted that consuming content in English helped them expand their vocabulary, understand different accents, and gain confidence in using the language. These results highlight the role of media-driven culture in informal language learning.